1999
DOI: 10.1111/j.1572-0241.1999.01213.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of A New Enzyme Immunoassay for Detecting Helicobacter Pylori in Feces: A Prospective Pilot Study

Abstract: HpSAT seems to be a reliable method for predicting H. pylori status in anti-H. pylori untreated patients. Conversely, the test appears less suitable to evaluate the outcome of the eradicating treatment. Consequently, it is likely to be accepted for the primary diagnosis of H. pylori status, particularly in dyspeptic young patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 8 publications
3
58
0
Order By: Relevance
“…H. pylori has been cultured from the feces of experimentally colonized individuals (13) and from children in The Gambia (20), but such culturing does not appear to be easy for the majority of patients. Several studies have detected H. pylori antigens in fecal material (15,22,23), but this technique cannot provide information beyond the presence or absence of antigens.…”
mentioning
confidence: 99%
“…H. pylori has been cultured from the feces of experimentally colonized individuals (13) and from children in The Gambia (20), but such culturing does not appear to be easy for the majority of patients. Several studies have detected H. pylori antigens in fecal material (15,22,23), but this technique cannot provide information beyond the presence or absence of antigens.…”
mentioning
confidence: 99%
“…Although some investigators have demonstrated that UBT and HpSA are absolutely equivalent in terms of sensitivity and specificity in the evaluation of eradication therapy, 15,23,24 others have documented a lower than expected reliability of HpSA in this setting. [25][26][27][28][29] It has been rightly emphasized that many studies on the performance of HpSA in post-treatment assessment have used UBT as the gold standard, and this has certainly diminished the meaning of the results. 30,31 However, the few studies using biopsy-based methods as the gold standard have provided conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the HpSA test was investigated for the diagnosis of H. pylori infection and the sensitivity and specificity were reported to be over 80% in symptomatic untreated patients (Makristathis et al 1998;Puspok et al 1999;Trevisani et al 1999;Vaira et al 1999). In our study, the sensitivity of the HpSA test was found and specificity.…”
Section: Discussionmentioning
confidence: 99%